2006
DOI: 10.1016/j.amjcard.2006.02.062
|View full text |Cite
|
Sign up to set email alerts
|

Relation of Brain Natriuretic Peptide Levels to Cognitive Dysfunction in Adults >55 Years of Age With Cardiovascular Disease

Abstract: Cardiovascular disease (CVD) is associated with cognitive deficits long before the onset of stroke or dementia. Recent work has extended these findings and shown that patients with congestive heart failure also exhibit reduced cognitive performance. Brain natriuretic peptide (BNP) is used to help diagnose heart failure, but no study has examined whether BNP predicts cognitive dysfunction in older patients with CVD. BNP values and performance on the Dementia Rating Scale were assessed in 56 older adults with do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
40
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(46 citation statements)
references
References 17 publications
6
40
0
Order By: Relevance
“…4,5 Hence, blood biomarkers of cardiovascular disease, such as N-terminal pro-brain natriuretic peptide (NT-proBNP) and high-sensitivity cardiac troponin T (hs-cTnT), have recently become of interest because of their upregulation not only in myocardial stress and injury but also in the early phases of cardiovascular disease. [6][7][8][9] Interestingly, higher levels of NT-proBNP and hs-cTnT were associated with cognitive impairment and dementia. 10 In addition to the traditional cerebral markers of vascular injury, such as lacunar infarcts and white matter hyperintensities, a novel marker of cerebrovascular diseases, cortical cerebral microinfarcts (CMIs), has recently gained attention because of its major role in cognitive impairment and dementia.…”
mentioning
confidence: 99%
“…4,5 Hence, blood biomarkers of cardiovascular disease, such as N-terminal pro-brain natriuretic peptide (NT-proBNP) and high-sensitivity cardiac troponin T (hs-cTnT), have recently become of interest because of their upregulation not only in myocardial stress and injury but also in the early phases of cardiovascular disease. [6][7][8][9] Interestingly, higher levels of NT-proBNP and hs-cTnT were associated with cognitive impairment and dementia. 10 In addition to the traditional cerebral markers of vascular injury, such as lacunar infarcts and white matter hyperintensities, a novel marker of cerebrovascular diseases, cortical cerebral microinfarcts (CMIs), has recently gained attention because of its major role in cognitive impairment and dementia.…”
mentioning
confidence: 99%
“…A study of 56 patients with dementia and cardiovascular disease showed cross sectional correlations of BNP with the conceptualization subtest of the Dementia Rating Scale score [21]. In 1066 elderly type 2 diabetics, those with higher NT-proBNP had lower scores on a cognitive battery, but this association was confounded by vascular and diabetes-related risk factors [22].…”
mentioning
confidence: 99%
“…Yet, patients with severe cardiovascular disease frequently exhibit cognitive problems in the absence of clinically identified stroke (Moser et al, 1999;Paul et al, 2005), particularly in cases of heart failure (Bennett & Sauve, 2003;Bornstein, Starling, Myerowitz, & Haas, 1995), presumably reflecting the impact of reduced cardiac function on the aging brain (Roman, 2004). We have previously shown that both cognitive dysfunction and structural brain abnormalities on magnetic resonance imaging (MRI) are associated with reduced cardiac output among patients with severe cardiovascular disease (Jefferson, Poppas, Paul, & Cohen, 2007a;Jefferson et al, 2007b) and abnormalities of systemic vascular function (Gunstad et al, 2006a;Gunstad et al, 2005;Gunstad et al, 2006b;Haley et al, 2007a;Haley et al, 2007b;Hoth et al, 2007). …”
mentioning
confidence: 99%